2003
DOI: 10.1039/b300759f
|View full text |Cite
|
Sign up to set email alerts
|

Structural studies of N-(2′-substituted phenyl)-9,10-dihydro-9,10-ethanoanthracene-11,12-dicarboximides by X-ray diffraction and NMR spectroscopy—proofs for CH/π interactions in liquid and solid phases

Abstract: N-(2 0 -R-Phenyl)-9,10-dihydro-9,10-ethanoanthracene-11,12-dicarboximides with R ¼ Me (1), OMe (2), OEt (3) and H (4) were investigated. The crystal and molecular structures of 1-3, determined by single crystal methods, show different conformations of the N-(2 0 -R-phenyl) group. Anti conformations and weak intermolecular CH/p contacts were found in 2 and 3, while anti and syn conformations coexist in 1 with CH/p contacts being absent. Solid-state 13 C CP/MAS spectra confirm the X-ray molecular structural data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 20 publications
2
18
0
Order By: Relevance
“…Even the C-HÁ Á ÁF contacts are comparable [C5-H5Á Á ÁF2 = 2.56 Å in (IIa) and C4-H4Á Á ÁF3 = 2.51 Å in (IIb), both along (Àx + 1, Ày + 1, Àz + 1)]. Similar structures with related cell parameters were also reported by Kishikawa et al (1997), Grossmann et al (2003) and Goh & White (2009).…”
Section: Commentsupporting
confidence: 79%
See 1 more Smart Citation
“…Even the C-HÁ Á ÁF contacts are comparable [C5-H5Á Á ÁF2 = 2.56 Å in (IIa) and C4-H4Á Á ÁF3 = 2.51 Å in (IIb), both along (Àx + 1, Ày + 1, Àz + 1)]. Similar structures with related cell parameters were also reported by Kishikawa et al (1997), Grossmann et al (2003) and Goh & White (2009).…”
Section: Commentsupporting
confidence: 79%
“…Moreover, anthracene-2,6dicarboxylate derivatives modified with maleimides have been used in poly(ethylene terephthalate) copolymers (Jones et al, 1999). Investigations of the conformational environment of the selected derivatives were described by Csö regh et al (2003), while Grossmann et al (2003) reported NMR spectroscopic analysis of the geometric features of the orthosubstituted molecules. Verma and co-workers reported several detailed studies on the analysis of the rotation around the C aryl -N bond in, for example, o-OMe-, o-Me-, o-Cl-and o-Brsubstituted N-arylimides with dynamic and temperature-dependent NMR spectroscopy (Verma & Singh, 1976, 1978Srivastava et al, 1991).…”
Section: Commentmentioning
confidence: 99%
“…1 . Previous studies by Harano et al , 15 Shimizu et al , 9 , 17 , 18 Verma et al , 19 Grossmann et al , 20 and Yamada et al 21 have demonstrated that N -arylimide molecular balances exhibit slow rotation about the C aryl –N imide bond at room temperature (Δ G ‡ ∼ 20 kcal mol –1 ). 9 , 22 The slowly rotating C aryl –N imide bond (indicated in red in Fig.…”
Section: Resultsmentioning
confidence: 96%
“…15 The rigid bicyclic framework fixes the position of most of the atoms, which greatly simplifies its conformational analysis. The only major degree of rotational freedom is the C−N single bond connecting the o-tolyl rotor to the succinimide ring.…”
mentioning
confidence: 99%